2015
DOI: 10.1371/journal.pone.0129049
|View full text |Cite
|
Sign up to set email alerts
|

Circulating B-Vitamins and Smoking Habits Are Associated with Serum Polyunsaturated Fatty Acids in Patients with Suspected Coronary Heart Disease: A Cross-Sectional Study

Abstract: The long-chain polyunsaturated fatty acids are considered to be of major health importance, and recent studies indicate that their endogenous metabolism is influenced by B-vitamin status and smoking habits. We investigated the associations of circulating B-vitamins and smoking habits with serum polyunsaturated fatty acids among 1,366 patients who underwent coronary angiography due to suspected coronary heart disease at Haukeland University Hospital, Norway. Of these, 52% provided information on dietary habits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Tobacco smoke contains a substantial number of reactive oxygen species that could trigger oxidative stress in the brain 60 , blood-brain-barrier 66 and periphery 67 , leading to vitamin B6 deficiency 67 . Of note, in humans, smoking reduced circulating plasma vitamin B6 and PLP levels 68,69 , with concentrations increasing significantly after a few days of smoking cessation 70 . This suggests that cigarette smoking could deplete circulating vitamin B6 and PLP levels by modifying the activity of the brain antioxidant defense triggered by PLP enzymatic interaction with SRR.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco smoke contains a substantial number of reactive oxygen species that could trigger oxidative stress in the brain 60 , blood-brain-barrier 66 and periphery 67 , leading to vitamin B6 deficiency 67 . Of note, in humans, smoking reduced circulating plasma vitamin B6 and PLP levels 68,69 , with concentrations increasing significantly after a few days of smoking cessation 70 . This suggests that cigarette smoking could deplete circulating vitamin B6 and PLP levels by modifying the activity of the brain antioxidant defense triggered by PLP enzymatic interaction with SRR.…”
Section: Discussionmentioning
confidence: 99%
“…Tsuge et al [ 8 ] further showed the lower contents of eicosapentaenoic acid (EPA; 20:5n-3), docosahexaenoic acid (DHA; 22:6n-3), and AA in plasma total lipids in B6-deficient male rats compared to pair-fed controls. Moreover, epidemiologic studies have indicated that low levels of circulating pyridoxal 5′-phosphate (PLP) change the compositions of PUFA in serum or plasma [ 9 , 10 , 11 , 12 ]. A clinical study with 23 healthy men and women combined (20–40 years) found that marginal vitamin B6 deficiency (plasma PLP concentration between 20 and 30 nmol/L), which was induced by a 28 day B6-restricted diet, reduced plasma concentrations of EPA, DHA, and AA and increased slightly plasma n-6/n-3 PUFA ratio [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A clinical study with 23 healthy men and women combined (20–40 years) found that marginal vitamin B6 deficiency (plasma PLP concentration between 20 and 30 nmol/L), which was induced by a 28 day B6-restricted diet, reduced plasma concentrations of EPA, DHA, and AA and increased slightly plasma n-6/n-3 PUFA ratio [ 10 ]. Thus, the data from animal and human studies thus far suggest that vitamin B6 deficiency may adversely affect PUFA compositions [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin B family members with antioxidant activity—folic acid, vitamin B2 (riboflavin), and vitamin B6 (pyridoxine)—are reduced in SMK compared with nonsmokers. 32 , 33 In this study, urinary levels of Vitamin B2- and B6-associated metabolite (pyridoxate) were increased following product switching to either VS Original or VS Menthol. Vitamin B2 acts as a cofactor for glutathione (GSH) reductase.…”
Section: Discussionmentioning
confidence: 59%